2016
DOI: 10.1080/13554794.2016.1242756
|View full text |Cite
|
Sign up to set email alerts
|

Motor simulation theories of musical beat perception

Abstract: There is growing interest in whether the motor system plays an essential role in rhythm perception. The motor system is active during the perception of rhythms, but is such motor activity merely a sign of unexecuted motor planning, or does it play a causal role in shaping the perception of rhythm? We present evidence for a causal role of motor planning and simulation, and review theories of internal simulation for beat-based timing prediction. Brain stimulation studies have the potential to conclusively test i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 84 publications
2
45
0
1
Order By: Relevance
“…This motor network includes the supplemental motor area (SMA), primary motor cortex, lateral premotor cortex, anterior cingulate, basal ganglia, and cerebellum (Repp and Su, 2013 ). Auditory rhythm perception activates the motor system and is closely linked to movement (Janata et al, 2012 ; Iversen and Balasubramaniam, 2016 ; Ross et al, 2016a , b ). The SMA is also strongly implicated in motor timing (Coull et al, 2016 ; Merchant and Yarrow, 2016 ), and along with the pre-SMA could be a hub of motor timing (Schwartze et al, 2012 ).…”
Section: Underlying Physiology Of the Auditory And Visual Timing Systmentioning
confidence: 99%
“…This motor network includes the supplemental motor area (SMA), primary motor cortex, lateral premotor cortex, anterior cingulate, basal ganglia, and cerebellum (Repp and Su, 2013 ). Auditory rhythm perception activates the motor system and is closely linked to movement (Janata et al, 2012 ; Iversen and Balasubramaniam, 2016 ; Ross et al, 2016a , b ). The SMA is also strongly implicated in motor timing (Coull et al, 2016 ; Merchant and Yarrow, 2016 ), and along with the pre-SMA could be a hub of motor timing (Schwartze et al, 2012 ).…”
Section: Underlying Physiology Of the Auditory And Visual Timing Systmentioning
confidence: 99%
“…Recently, intracranial depth-electrode EEG recordings in humans revealed that processes from the earliest auditory cortical areas (Heschl's gyrus) shape the neural representation of rhythmic inputs in favour of increased relative amplitude of the activity corresponding to meter-related frequencies (Nozaradan et al, 2016c). This selective enhancement of meter-related frequencies may require connections between the auditory cortex and other brain structures such as the premotor cortex, the basal ganglia and the supplementary motor area, which are involved in beat-based timing (Grahn, 2012;Merchant & Honing, 2014;Patel & Iversen, 2014;Ross et al, 2016;Nozaradan et al, 2017b). However, this selective enhancement may also be the product of lower-level properties of auditory neurons that process sound input before the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation, or more broadly described by action-perception coupling, has in recent years found increasing support in musical contexts (Maes et al 2014;. One aspect of music cognition, the processing of rhythm, seems to be suitably accommodated in the framework of motor simulation (Ross et al 2016). The Action Simulation for Auditory Prediction (ASAP) hypothesis (Patel and Iversen 2014) postulates that, upon hearing a musical rhythm and without explicit movement, the motor system internally simulates a periodic body motion that corresponds to the most salient periodicity of the rhythmits beat.…”
Section: Introductionmentioning
confidence: 99%